(untitled) (The Review of Diabetic Studies, 2025)
Diabetes mellitus affects over 537 million adults worldwide; therefore, reliable and continuous glucose monitoring systems are essential. However, traditional enzymatic glucose sensors face several limitations, including enzyme instability, temperature sensitivity, and interference from environmental factors. Consequently, recent research has shifted focus toward developing non-enzymatic electrochemical glucose sensors based on nanomaterials. A systematic literature review covering publications from 2018 to 2024 reveals that these non-enzymatic sensors offer superior stability and operate effectively within a broader pH range compared to their enzymatic counterparts. Moreover, they demonstrate enhanced sensitivity, with detection limits as low as 0.1 μM and linear ranges extending up to 30 mM. Key nanomaterials employed include noble metal nanoparticles, such as Au, Pt, and Pd, as well as transition metal oxides like NiO, CuO, and Co₃O₄, and hybrid nanocomposites. Ultimately, non-enzymatic electrochemical glucose sensors represent a promising direction for next-generation diabetes monitoring, providing improved stability, cost-effectiveness, and the potential for continuous monitoring applications.